Biomonitoring of volatile organic compounds (VOCs) among hairdressers in salons primarily serving women of color: A pilot study. (September 2021) - Louis, Lydia M.; Kavi, Lucy K.; Boyle, Meleah; Pool, Walkiria; Bhandari, Deepak; De Jesús, Víctor R.; Thomas, Stephen; Pollack, Anna Z.; Sun, Angela; McLean, Seyrona; Rule, Ana M.; Quirós-Alcalá, Lesliam
Highlights: This is the first VOC biomonitoring study among female hairdressers of color. Higher VOC biomarker concentrations in hairdressers serving Black versus Latino clientele. Select salon services were associated with higher VOC biomarker concentrations. Hairdressers had higher concentrations for several VOC biomarkers than office workers. Hairdressers had higher concentrations for several VOC biomarkers than U.S. women. Abstract: Hairdressers are exposed to volatile organic compounds (VOCs), many of which have been linked to acute and chronic health effects. Those hairdressers serving an ethnic clientele may potentially experience disproportionate exposures from frequent use of products containing VOCs or different VOC concentrations contained in products which are marketed to the specific needs of their clientele. However, no biomonitoring studies have investigated occupational exposures in this population. In the present pilot study, we sought to characterize concentrations and exposure determinants for 28 VOC biomarkers in post-shift urine samples among 23 hairdressers primarily serving an ethnic clientele. VOC biomarker concentrations among hairdressers of color were compared to concentrations among a comparison group of 17 office workers and a representative sample of women participating in the U.S. National Health and Nutrition Examination Survey. VOC biomarkers were detected in all hairdressers with higher concentrations observed among hairdressers serving a predominantly Black versus Latino clientele, and among hairdressers overall versus office workers and women in the U.S. general population. Median biomarker concentrations for acrolein, 1, 3-butadiene, and xylene in hairdressers were more than twice as high as those observed among office workers. Median concentrations for 1-bromopropane, acrolein and 1, 3-butadiene were more than four times higher among all hairdressers compared to those reported among women in the U.S. general population. Select salon services (e.g., sister locs, flat ironing, permanent hair coloring, permanent waves or texturizing, Brazilian blowout or keratin treatment, etc.) were also associated with higher VOC biomarker concentrations among hairdressers. This pilot study represents the first biomonitoring analysis to characterize VOC exposures among women hairdressers of color and to provide evidence that this occupational population may experience elevated VOC exposures compared to women in the U.S. general population. Results from our study represent an important first step in elucidating occupational VOC exposures in this understudied occupational group. Larger studies among a racially and ethnically diverse cohort of hairdressers are warranted to confirm our findings and inform future exposure interventions in this understudied occupational population.